Acute ischaemic lesions are associated with cortical superficial siderosis in spontaneous intracerebral hemorrhage. (18th December 2018) - Revel‐Mouroz, P.; Viguier, A.; Cazzola, V.; Calviere, L.; Patsoura, S.; Rousseau, V.; Sommet, A.; Albucher, J. F.; Cognard, C.; Olivot, J. M.; Bonneville, F.; Raposo, N.
Abstract : Background and purpose: Diffusion‐weighted imaging (DWI) commonly detects acute ischaemic lesions in patients with acute intracerebral hemorrhage (ICH), especially with cerebral amyloid angiopathy (CAA). We investigated the relationship between cortical superficial siderosis (cSS), a neuroimaging marker of CAA, and DWI lesions in patients with acute ICH. Methods: We conducted a retrospective analysis of prospectively collected data from consecutive patients with acute supratentorial ICH who underwent brain magnetic resonance imaging within 10 days after symptom onset. Magnetic resonance imaging scans were analyzed for DWI lesions, cSS and other markers for small‐vessel disease. Univariate and multivariate analyses were performed to assess the association between cSS and DWI lesions. Results: Among 246 ICH survivors (mean age 71.4 ± 12.6 years) who were enrolled, 126 had lobar ICH and 120 had deep ICH. Overall, DWI lesions were observed in 38 (15.4%) patients and were more common in patients with lobar ICH than deep ICH (22.2% vs. 8.3%; P = 0.003). In multivariate logistic regression analysis, the extent of white matter hyperintensities [odds ratio (OR), 1.29; 95% confidence interval (CI), 1.05–1.58; P = 0.02] and cSS severity (focal cSS: OR, 3.54; 95% CI, 1.28–9.84; disseminated cSS: OR, 4.41; 95% CI, 1.78–10.97; P = 0.001) were independently associated with the presence of DWI lesions. Conclusions: Diffusion‐weighted imaging lesions are more frequently observed in patients with acute lobar ICH than in those with deep ICH. cSS severity and white matter hyperintensity extent are independent predictors for the presence of DWI lesions, suggesting that CAA may be involved in the pathogenesis of DWI lesions associated with acute ICH.